Teleophthalmology: improving patient outcomes? - Sreelatha OK (Dove Medical Press, 2016)
Omana Kesary Sreelatha,1 Sathyamangalam VenkataSubbu Ramesh2 1Ophthalmology Department, Sultan Qaboos University Hospital, Muscat, Oman; 2Department of Optometry, School of Allied Health Sciences, Manipal University, Manipal, India Abstract: Teleophthalmology is gaining importance as an effective eye care delivery modality worldwide. In many developing countries, teleophthalmology is being utilized to provide quality eye care to the underserved urban population and the unserved remote rural population. Over the years, technological innovations have led to improvement in evidence and teleophthalmology has evolved from a research tool to a clinical tool. The majority of the current teleophthalmology services concentrate on patient screening and appropriate referral to experts. Specialty care using teleophthalmology services for the pediatric group includes screening as well as providing timely care for retinopathy of prematurity (ROP). Among geriatric eye diseases, specialty teleophthalmology care is focused toward screening and referral for diabetic retinopathy (DR), glaucoma, age-related macular degeneration (ARMD), and other sight-threatening conditions. Comprehensive vision screening and refractive error services are generally covered as part of most of the teleophthalmology methods. Over the past decades, outcome assessment of health care system includes patients’ assessments on their health, care, and services they receive. Outcomes, by and large, remain the ultimate validators of the effectiveness and quality of medical care. Teleophthalmology produces the same desired clinical outcome as the traditional system. Remote portals allow specialists to provide care over a larger region, thereby improving health outcomes and increasing accessibility of specialty care to a larger population. A high satisfaction level and acceptance is reported in the majority of the studies because of increased accessibility and reduced traveling cost and time. Considering the improved quality of patient care and patient satisfaction reported for these telemedicine services, this review explores how teleophthalmology helps to improve patient outcomes. Keywords: teleophthalmology, patient satisfaction, patient outcomes, tele-ROP, tele–diabetic retinopathy, teleglaucoma